ARAH KEBIJAKAN PERTAMBANGAN UNTUK PEMBANGUNAN BERKELANJUTAN (STUDI KASUS PERIZINAN USAHA TAMBANG BATUAN PASCA UNDANG UNDANG NOMOR 23 TAHUN 2004 DI KABUPATEN ROKAN HULU RIAU) - Hayatul Ismi; Nofrizal Nofrizal; Almadison Almadison (Fakultas Hukum Universitas Riau, 2022)
The legal principles of mining management in Law no. 4 of 2009 concerning mineral and coal mining based on the principles of benefit, fairness, and balance; siding with the interests of the nation; participatory, transparency, and accountability; sustainable and environmentally sound. The concept of sustainable development is not only a balance between economic, social and environmental in an effort to carry out existing development, but also emphasizes efforts to accommodate the principle of justice between generations. The purpose of this paper is to find out the direction of mining policy for sustainable development (a case study of rock mining business licensing after Law number 23 of 2004 in Rokan Hulu Regency, Riau), so that what happened in Rokan Hulu Regency experienced a buildup of Mining Business Permits with the transition of management The permission. From this writing, it is hoped that the Mining Business Permit policy can be carried out properly so that mining for sustainable development can be realized